ダイ41ジ ナンキョク チイキ カンソクタイ ニ オイテ ジッシ サレタ ナンキョク ヒョウショウ ジョウ ニオケル GPS カンソク - 土井, 浩一郎; ドイ, コウイチロウ; 今栄, 直也; イマエイ, ナオヤ; 岩田, 尚能; イワタ, ナオヨシ; 瀬尾, 徳常; セオ, ノリツネ; Doi, Koichiro; Imaei, Naoya; Iwata, Naoyosi; Seo, Noritsune (2004)
P(論文) 第41次南極地域観測隊における越冬期間中に,南極大陸氷床上の3点,すなわち,とっつき岬付近の裸氷帯N7,みずほ基地,やまと航空拠点YM175においてGPS観測を行い,各点の流動速度を求めた.N7の移動速度はN60°Wの方向に約1.5cm/dayであった.みずほ基地の移動速度はN60°Wの方向に約6cm/dayという値であり,H. Motoyama et al.(Nankyoku Shiryo, 39, 94, 1995)が得た結果とよく一致している.YM175ではN71°Wの方向へ0.8mm/dayという水平方向の速度とともに,1.1mm/dayの上昇速度という結果を得た.この上昇運動はやまと山脈地域において提案されている隕石集積機構を支持するものである. We conducted GPS observations at three sites on the Antarctic ice sheet during wintering of the 41st Japanese Antarctic Research Expedition (JARE-41). The three sites are N7 (vicinity of coastline), Mizuho Station (260km inland on the ice sheet), and YM175 (bare ice field near the Yamato Mountains). Continuous data for more than four days were obtained and velocity vectors were determined with reference to the Syowa International GPS Service for Geodynamics (IGS) site using a precise ephemeris. The obtained velocity at N7 was 1.5cm/day and the direction was N60°W. At Mizuho Station, the observed velocity was 6cm/day and the direction was N60°W. These values showed good agreement with previous observations by H. Motoyama et al. (Nankyoku Shiryo, 39, 94, 1995). At YM175, continuous observation for more than 10 days was carried out; observed vertical and lateral displacements were about 1cm. The considerable upward displacement as well as the small lateral displacement supports the meteorite accumulation hypothesis for the Yamato Mountains region. departmental bulletin paper